1979
DOI: 10.2134/agronj1979.00021962007100060004x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Spring Barley in Narrow Rows1

Abstract: Several researchers in the U. S. and Canada have investigated the effect of row spacing on yield and other agronomic traits of small grains with variable results. The objective of this study was to compare the performance of spring barley (Hordeum vulgare L. emend Bowden) seeded in a very narrow row spacing (7.5 cm) with two row spacings (15 and 30 cm) commonly used in production agriculture and in experimental research. Three genotypes were planted at Madison, WI, in 1975 and 1976, in a St. Charles silt loam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…Overall, differences in kernel weight, plumpness, and test weight between the two DR placements were limited, and where differences did occur, they were not consistent over site-years. Brinkman et al (1979), Lafond (1994), and Siemens (1963) also found that kernel weight was similar among several row spacings for barley, although Siemens (1963) found a slight increase in kernel weight for barley as row spacing increased from 15 to 76 cm.…”
Section: Fig 4 Mean Barley Kernel Weight (A) Percent Plump Kernelsmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, differences in kernel weight, plumpness, and test weight between the two DR placements were limited, and where differences did occur, they were not consistent over site-years. Brinkman et al (1979), Lafond (1994), and Siemens (1963) also found that kernel weight was similar among several row spacings for barley, although Siemens (1963) found a slight increase in kernel weight for barley as row spacing increased from 15 to 76 cm.…”
Section: Fig 4 Mean Barley Kernel Weight (A) Percent Plump Kernelsmentioning
confidence: 89%
“…The most common seed-placement configurations used with air seeding equipment involves knife openers, with a narrow (2-cm) seed band generated at a 23-or 30-cm row spacing, and sweep openers equipped with boots that spread seed in a 15-to 23-cm band. Research into the potential benefits of seed-placement configurations or narrow-versus wide-row-spacing options has primarily focused on agronomic responses (Brinkman et al 1979;Deibert 1993;Johnston and Stevenson 2001;Lafond 1994;Lafond and Derksen 1996;Siemens 1963). However, seed placement and row spacing can also affect infection and the spread of plant diseases (Tompkins 1990;Tompkins et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Total biomass production of PC rye did not appear to be affected by row spacing (Table 2). However, it has been observed that crops seeded in narrow rows often yield more and compete more favourably with weeds than crops grown in wide rows (Brinkman et al 1979;Moyer et al 1991). Also, some annual cereals lodge less in narrow rows (Brinkman et al 1979).…”
Section: Effect Of Date Of Seeding and Row Spacing On Forage Yieldmentioning
confidence: 99%
“…However, it has been observed that crops seeded in narrow rows often yield more and compete more favourably with weeds than crops grown in wide rows (Brinkman et al 1979;Moyer et al 1991). Also, some annual cereals lodge less in narrow rows (Brinkman et al 1979). Tests conducted at Lethbridge show that PC rye competed well with weeds regardless of row spacing and small weed populations did not influence its forage quality or biomass production in subsequent years (Moyer et al 2002).…”
Section: Effect Of Date Of Seeding and Row Spacing On Forage Yieldmentioning
confidence: 99%
“…Under weed-free conditions, a wider (30 cm) compared with narrower (15-18 cm) row spacing decreased barley grain yield by 7-13% in some studies (Siemens 1963;Finlay et al 1971;Brinkman et al 1979), but in other studies row spacing had no effect on barley yield in conventional or direct seeding systems (Young and Bauer 1991;Lafond 1994). Wheat (Triticum aestivum L.) grain yield did not differ between a spread band (20-cm spread) and distinct row seed placement at either a 23-or 30-cm row spacing (Johnston and Stevenson 2001).…”
Section: Mots Clésmentioning
confidence: 99%